Prostate Cancer Stem Cells: Clinical Aspects and Targeted Therapies - Wolf, Isis; Gratzke, Christian; Wolf, Philipp (Frontiers in Oncology, 2022)
Despite decades of research and successful improvements in diagnosis and therapy, prostate cancer (PC) remains a major challenge. In recent years, it has become clear that PC stem cells (PCSCs) are the driving force in tumorigenesis, relapse, metastasis, and therapeutic resistance of PC. In this minireview, we discuss the impact of PCSCs in the clinical practice. Moreover, new therapeutic approaches to combat PCSCs are presented with the aim to achieve an improved outcome for patients with PC.